Pendidikan Karakter di Sekolah Dasar Islam Terpadu: Kajian Literatur Sistematis - Irfan Sofian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education is a fundamental aspect of the Indonesian education system, particularly in addressing moral and social challenges in the modern era. The increasing cases of bullying, intolerance, consumerism, and declining social responsibility among students reflect a character crisis that demands immediate intervention. In response, the Indonesian government issued Presidential Regulation No. 87 of 2017 concerning the Strengthening of Character Education (PPK), emphasizing the shared responsibility of families and schools in cultivating character through curriculum, habituation activities, and teacher role modeling. One prominent societal response to this need is the development of Integrated Islamic Elementary Schools (SD IT), which combine national curricula with Islamic values through an integrative approach. This study aims to examine the trends in character education implementation in SD ITs across Indonesia using a Systematic Literature Review (SLR) approach. A total of 10 peer-reviewed articles published between 2020 and 2025 were analyzed thematically to identify approaches, core values, strategies, and challenges related to character education. The findings reveal that effective character formation in SD ITs involves collaboration between teachers and parents, modeling by teachers, project-based learning, Quran-based instruction, and integration of pesantren-based extracurricular activities. The success of these efforts is closely tied to contextual understanding, cultural integration, and consistency in implementation. This study contributes theoretically by enriching the discourse on Islamic character education and practically by offering insights for educators and policymakers in designing more effective and contextualized character education programs in elementary Islamic schools.